Decarbonising the refinery sector: A socio-technical analysis of advanced biofuels, green hydrogen and carbon capture and storage developments in Sweden. (February 2022) - Nurdiawati, Anissa; Urban, Frauke
Abstract: The oil refinery industry is one of the major energy users and responsible for a large proportion of greenhouse gas (GHG) emissions. This sector is facing multiple sustainability-related transformation pressures, forcing the industry to adapt to changing market conditions. The transition to a low-carbon economy will require oil refineries to adopt decarbonisation technologies like advanced biofuels, green hydrogen and carbon capture and storage (CCS). However, the development and implementation of these technologies is not a straightforward process and may be inhibited by lock-in and path dependency. This paper draws on expert interviews and combines the Technological Innovation Systems (TIS) and Multi-level Perspective (MLP) frameworks to examining the niche level development of three emerging technologies in the context of deep decarbonisation of refinery. This research finds that the development of the three decarbonisation technologies shares some of the challenges and opportunities and exhibits technology interdependency to some extent. Among the three TISs, advanced biofuel is the most mature in terms of knowledge base, actor-network, legislation framework and market function. Green hydrogen and CCS encounter stronger momentum than before and can benefit from possible synergies across various sectors. However, the analysis also reveals the lack of market formation, mainly due to the lack of policy instruments for niche markets. Here, policy recommendations for accelerating deep decarbonisation of the oil refinery industry are discussed. Finally, we contribute to the sustainability transitions literature by exploring the dynamics of emerging TISs for industrial decarbonisation.